Unlocking the therapeutic potential of primary tumor-draining lymph nodes - Rotman, Jossie; Koster, Bas D.; Jordanova, Ekaterina S.; Heeren, A. Marijne; de Gruijl, Tanja D. (Cancer Immunology, Immunotherapy, 2019)
Lymph nodes draining the primary tumor are essential for the initiation of an effective anti-tumor T-cell immune response. However, cancer-derived immune suppressive factors render the tumor-draining lymph nodes (TDLN) immune compromised, enabling tumors to invade and metastasize. Unraveling the different mechanisms underlying this immune escape will inform therapeutic intervention strategies to halt tumor spread in early clinical stages. Here, we review our findings from translational studies in melanoma, breast, and cervical cancer and discuss clinical opportunities for local immune modulation of TDLN in each of these indications.